(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Implementing Quality Management Systems (QMS) and achieving accreditation under the ISO/IEC 17025 standard can be particularly challenging for laboratories within teaching and research institutions. During the process of implementing QMS in two testing laboratories, innovative solutions were developed to address the unique challenges posed by this environment. The experience gained from this initiative resulted in the development of a set of general steps, grounded in a process approach, that are detailed in this article. These steps aim to assist laboratories striving for accreditation by utilizing strategic planning data, aligning QMS objectives with corresponding processes, and defining indicators to track system performance and drive improvements.